Analysis of land-atmosphere interactions and their influence on the energy and water cycle over the Tibetan Plateau - Yaoming Ma; Zhongbo Su; Lei Zhong; Yijian Zeng; Xuelong Chen; Cunbo Han; Binbin Wang; Zhipeng Xie; Weiyao Ma; Longtengfei Ma; Qianqian Han; Ruodan Zhuang; et al. (Geo-spatial Information Science, 2024)
The Tibetan Plateau (TP) has been the focus of numerous studies examining the energy and water cycle variations, but there is still a lack of long-term, quantitative precise assessments of evapotranspiration. This research first provided two sets of long-term comprehensive observational datasets, and an advanced monitoring technique to measure soil moisture, which can improve the estimation accuracy of evapotranspiration. Subsequently, using microwave data, the Surface Energy Balance System model and Machine Learning methods, it calculated a complete set of long-term evapotranspiration data. At the same time, based on reasonable assumptions, it also estimated the total evaporation from plateau lakes. These findings contribute significantly to the understanding of the relationship between the Asian monsoon, the TP’s physical characteristics, and its atmosphere, thereby improving predictions of water resource variability in the TP. The study’s innovative methodologies and synthesis of diverse data sources provide critical information for informed and sustainable water management strategies in the region.